Arte nell'arte Ceramiche medievali lette attraverso gli occhi dei grandi maestri toscani del Trecento e del Quattrocento - Degasperi, Angelica (Strumenti per la didattica e la ricerca, 2016)
The volume analyses the representation of ceramic artefacts appearing in some Tuscan artistic works dating back to the 14th and 15th century and aims to combine the data emerging from iconographic sources with those relating to material and written documentation. It also aims to grasp the potential of iconography, trying to understand the extent to which it is possible to identify archaeologically well-defined cultural areas; it also attempts to establish whether the representations of specific details of everyday life correspond to a realistic description of everyday life itself, or rather are a reflection of feelings of curiosity, amazement, ambition or appreciation for the beauty of the objects. The study highlights how iconography is able to integrate our knowledge on the medieval ceramic productions and on the social context of use of specific vascular forms and types.